Application of Comprehensive Electromagnetic Methods in the Search for Copper-Nickel Polymetallic Ores in Shallow-Covered Areas: A Case Study of The Jing'erquan Area in the East Tianshan Mountains of Xinjiang - Shihao JIA; Yong LI; Shengping GONG; Keqiang ZHAO; Hongyu GUO (CT Lilun yu yingyong yanjiu)
The Jing'erquan area in the East Tianshan Mountains of Xinjiang is characterized by shallow coverage, posing challenges to surface geological exploration for ore bodies. This study utilized a combination of geophysical methods to overcome these challenges. Magnetic anomaly mapping was used initially to delineate areas of interest, followed by the application of the high-power time-domain induced polarization (TDIP) method to estimate mineralization extents and structural distributions within the mining area. Subsequently, the controllable source electromagnetic sounding method was employed to generate resistivity section maps, revealing subsurface structural characteristics and ore body occurrences. Comprehensive data processing and interpretation identified two magnetic anomalies and four IP anomalies. The results of these applications provide foundational support for future drilling projects within the mining area and offer valuable insights for workers in similar regions seeking copper–nickel polymetallic deposits.